Of Ponzi schemes and investment scams: a case study of enforcement actions in Malaysia - Mohd. Sulaiman, Aiman @ Nariman; Moideen, Azza Isma; Moreira, Sharon David (Emerald Insight, 2016)
This paper aims to chart the enforcement actions taken by the Malaysian regulatory authorities in relation to illegal investment schemes in Malaysia, and clarifies the various strategies adopted by the Malaysian regulatory authorities to ensure protection of investors in the capital market.The enforcement actions relate to the Swiss cash scheme as well as commodities futures involving crude palm oil and a more recent case involving gold futures. These schemes share similar characteristics with Ponzi schemes that were thrust into the international limelight in the notorious Madoff Ponzi scheme and its allegation of regulatory failure.